Revolution in the air : the songs of Bob Dylan 1957-1973 - Heylin, Clinton (Chicago Review Press, 2009)
A comprehensive book on Bob Dylan's song lyrics, this volume arranges the more than 300 songs by the date they were actually written rather than when they appeared on albums.